Reducing Golden Hour Admission Times for Extremely Preterm Infants: An Improvement Science Initiative - Heitkamp, Nicholas M.; Fox, Hannah; Elliott, Megan; Swanson, Jonathan R.; Lepore, Sarah; Zanelli, Santina A.; Wiggins, Jaclyn B. (American Journal of Perinatology, 2025)
The Golden Hour is the first 60 minutes of life for extremely preterm infants and represents a critical window where timely stabilization can reduce morbidity such as intraventricular hemorrhage and bronchopulmonary dysplasia. At the University of Virginia, average Golden Hour admission times for infants <28 weeks' gestation were 117 minutes, indicating a major opportunity for improvement. This study aimed to reduce admission time by 25% (to ≤87 min) for infants <28 weeks' gestational age within 1 year of implementation.Using the Institution for Healthcare Improvement methodology, a multidisciplinary team identified key drivers of delay and implemented two Plan-Do-Study-Act (PDSA) cycles. PDSA 1 introduced a designated admission coordinator, structured flowsheet, and visible timer to enhance team awareness. PDSA 2 focused on line-placement efficiency, adding an auditory time, team huddles after 15 minutes, and earlier isolette closure to promote thermoregulation. Statistical process control (SPC) charts (XbarS, XmR) were used to evaluate changes. The outcome measure was time from admission to isolette closure. Process measures were time to glucose, IV dextrose, X-ray, and surfactant administration. Balancing measures were admission temperature, glucose levels, and severe intraventricular hemorrhage (IVH) rates.Among 106 infants, the average admission time decreased from 117 to 59 minutes, resulting in a 50% reduction. The proportion of admissions meeting the SMART aim (<87 min) improved from 8 to 100%. Process variability decreased on both XbarS and XmR charts. Balancing measures remained stable.Two sequential PDSA cycles achieved and sustained a 50% reduction in Golden Hour admission time without adverse effects. Structured team roles, real-time feedback, and workflow redesign produced a more efficient and stable process. This initiative demonstrates that systematic QI can meaningfully optimize Golden Hour care and may be replicable across NICUs.
Keywords: extremely preterm infant; Golden Hour; quality improvement; improvement science; statistical process control; neonatal intensive care unit